2008
DOI: 10.1136/adc.2008.142836
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease and stroke

Abstract: Stroke and cerebrovascular disorders are important causes of morbidity and mortality in children; they are already amongst the top 10 causes of childhood death and are probably increasing in prevalence. Acute treatment of stroke syndromes in adults is now evidence based. However, paediatric stroke syndromes are far less common and the differential diagnosis is very wide, but the individual health resource implications are much greater because of the life-long treatment costs in survivors. Recognition and consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 51 publications
0
36
0
1
Order By: Relevance
“…74 All guidelines agree on not recommending fibrinolytic therapy with tPA or alteplase for childhood arterial ischemic stroke, except for cases occurring within 3 hours after stroke. 79 As prevention of stroke, AHA 77 and ACCP 76 recommend anticoagulation therapy only for selected prothrombotic states, although IBD is not specifically cited; UK-RCP 74 advises referral to a hematologist. Thrombophilic screening and alternatives to oral contraception are recommended only after a first TE event, 77 and they are not specifically discussed for IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…74 All guidelines agree on not recommending fibrinolytic therapy with tPA or alteplase for childhood arterial ischemic stroke, except for cases occurring within 3 hours after stroke. 79 As prevention of stroke, AHA 77 and ACCP 76 recommend anticoagulation therapy only for selected prothrombotic states, although IBD is not specifically cited; UK-RCP 74 advises referral to a hematologist. Thrombophilic screening and alternatives to oral contraception are recommended only after a first TE event, 77 and they are not specifically discussed for IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…ACVD accounts for 10% of mortality among all diseases and is one of the three major causes of mortality in humans (18). Additionally, ACVD events result in high rates of disability due to lasting neurological damage (2).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CVD is typically associated with ischemic stroke [4] . Ischemic stroke featuring functional disturbance and morphological damage of brain is caused by CVD, which affects the brain blood supply and leads to a cascade of metabolic alterations.…”
Section: Introductionmentioning
confidence: 99%